2015
DOI: 10.1080/03650340.2015.1017569
|View full text |Cite
|
Sign up to set email alerts
|

Crop rotation effects on yield of oilseed rape, wheat and barley and residual effects on the subsequent wheat

Abstract: Economic conditions are forcing farmers to grow crops with high revenue leading to cereal-dominated crop rotations with increasing risk due to unfavourable preceding crops or preceding crop combinations. Based on a long-term field trial (1988)(1989)(1990)(1991)(1992)(1993)(1994)(1995)(1996)(1997)(1998)(1999)(2000)(2001) with 15 different rotations including winter oilseed rape (OSR), winter wheat, winter barley, spring peas and spring oats, the effects of different preceding crops, prepreceding crops and crop … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
61
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(69 citation statements)
references
References 27 publications
5
61
1
2
Order By: Relevance
“…The influence of variable organic fertilization on the crop yield of maize has been confirmed by the studies of Sieling, Christen [21], Ren et al [22] and Millar et al [23]. The crop yield of Brassica napus L. indicated a clear differentiation and was influenced by the type of compost (C 1 -C 6 ) as well as mineral fertilization (Fig.…”
Section: Resultssupporting
confidence: 55%
“…The influence of variable organic fertilization on the crop yield of maize has been confirmed by the studies of Sieling, Christen [21], Ren et al [22] and Millar et al [23]. The crop yield of Brassica napus L. indicated a clear differentiation and was influenced by the type of compost (C 1 -C 6 ) as well as mineral fertilization (Fig.…”
Section: Resultssupporting
confidence: 55%
“…Carr et al (2008) suggested that wheat grain yield was 524 to 739 kg/ha greater in the winter wheat-field pea rotation compared with winter wheat-winter wheat rotation from 2000 to 2003, depending on the year. Similarly, Sieling and Christen (2015) suggested that unfavourable preceding crops significantly decreased the yield of winter wheat by 10% on average, however, with a large year-to-year variation. In double-cropping system, in which cereals and legumes were associated, the winter wheat yield was reduced by 50% or more in comparison with control plots (Sarunaite et al 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Average share of grains 2.8 + 2.5 mm sieve in years after both preceding crops -different literae -significant difference at the level α = 0.05; equal literae -insignificant difference at the level α = 0.05. cally significantly higher (51.2 g) than after preceding crop of winter barley (48.6 g). Sieling and Christen (2015) investigated the effects unfavourable preceding crops on the grain yield of winter oilseed rape, winter wheat and winter barley. Wheat as the preceding crop mainly decreased the 1,000 grain weight, and to a lesser extent, the ear density of the subsequent wheat crop.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, increased use of fertiliser and pesticide inputs may offset the effects on yield decline to some extent, but is simultaneously contrary to societal and political aims such as preservation of existing biodiversity, mitigation of climate change and protection of water bodies and drinking water sources (Geiger et al 2010;Richter et al 2013). It is well known in Germany and elsewhere that, unlike cereal monoculture, wheat grown after oilseed rape (OSR) yields more than wheat grown after cereals (Angus et al 2015;Sieling & Christen 2015). The mechanisms behind the break crop benefits (BCB) of OSR for wheat are improved soil structure, better weed control, suppression of propagation by typical cereal pathogens and avoidance of phytotoxic exudates released by harvest residues, which are suspected to inhibit development of juvenile wheat plants sown after wheat (Kirkegaard et al 2008).…”
Section: Introductionmentioning
confidence: 99%